If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(2x + x) = x + (3x + -5) Combine like terms: 2x + x = 3x 5x + -1(3x) = x + (3x + -5) Remove parenthesis around (3x) 5x + -1 * 3x = x + (3x + -5) Multiply -1 * 3 5x + -3x = x + (3x + -5) Combine like terms: 5x + -3x = 2x 2x = x + (3x + -5) Reorder the terms: 2x = x + (-5 + 3x) Remove parenthesis around (-5 + 3x) 2x = x + -5 + 3x Reorder the terms: 2x = -5 + x + 3x Combine like terms: x + 3x = 4x 2x = -5 + 4x Solving 2x = -5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2x + -4x = -5 + 4x + -4x Combine like terms: 2x + -4x = -2x -2x = -5 + 4x + -4x Combine like terms: 4x + -4x = 0 -2x = -5 + 0 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5
| 4+P*0.0381/12 | | 61y=10 | | -7f=2*-7+8 | | 7(6x-5)+15x= | | 2l+2(70)=800 | | -9/7=-2x-x | | x-6=x-9 | | (w-5)(w+5)= | | 8=-5t-2 | | 4=3x/4-2 | | -2/x | | -125/x=-21 | | 6(2x+3)=24 | | -6u-30=0 | | 3z^2-10z+3=0 | | 4t+12=0 | | -0.75x-47.77=-27.27-4.85x | | 1-1/4 | | 4z^2-4z-48=0 | | -2-(-3)-3= | | 1/2-2/1+3/4 | | 8+x-8+2+6+x-4= | | 2n-4(n-6)=1/2(-4n-5) | | 6t-20=-8 | | n^3-20n^2-5=0 | | 5(3b-3)-3(3b-7)=12 | | 6x^2+-7x^2= | | -14=-8u+15 | | -0.5t-3.7=-0.7 | | x+55.5=-x-44.5 | | 35000-8t=0 | | x+555=-x-445 |